Ecological methods of weed control in paulownia (Paulownia tomentosa) plantations - Nychkaliuk , H. (Quarantine and plant protection, 2024)
Goal. To study the dynamics of weed infestation in young paulownia (Paulownia tomentosa) plantations and develop a weed control system that ensures the successful growth and development of paulownia plantations. To investigate the possibility of using environmentally friendly methods of weed control in the paulownia plantations in the Forest Steppe zone of Ukraine. Methods. Field methods were used in the experiment. The statistical processing of the experimental data was performed using Microsoft Office Excel. Results. The experiment was carried out to study weed control methods and ensure efficient use of soil water. The soil in the plant zone was mulched with straw (10 cm layer), covered with black polyethylene (25 mkm) film or spanbond (100 g/ m2). In the young paulownia plantations of the 10th year of cultivation, where no weed control measures were applied, the active growth of weeds was observed. The highest number of weeds was represented by Setaria glauca L. (17.5 plants/ m2), Echinochloa crus-galli (25.2 plants/ m2), Chenopodium album (15.1 plants/ m2), Elymus repens (21.2 plants/ m2), Sinapis arvensis (7.0 plants/ m2), Convolvulus arvensis (6.7 plants/ m2), and others. Conclusions. It was found that the mulching of young paulownia plantations with straw (10 cm layer) is an effective practice that ensures a high productivity of paulownia, with a plant height of 166 cm. The most effective method was covering the soil with black polyethylene film, with a plant height of 173 cm.